Digital Psychology and Consumer Purchasing Behavior: A Quantitative Analysis of Jumia Customers in Ilaro, Ogun State, Nigeria - Borishade, Taiye; Akinleke, Yetunde O.; Kehinde, Oladele J. (Economics, Business and Management Science Journal, 2026)
The study seeks to examine the effect of digital psychology on consumer purchasing behavior among Jumia consumers in Ilaro, Ogun State, Nigeria. A descriptive survey research design was used in the study, whereby 384 respondents were administered structured questionnaires to collect data. In line with the objectives of the study, digital psychology was measured using two constructs: social proof and emotional trigger. Multiple regression analysis was used to examine the relationship between digital psychology and consumer purchasing behavior among Jumia consumers in Ilaro, Ogun State, Nigeria, using SPSS version 27 software. Results from the analysis show that digital psychology had a significant positive relationship with consumer purchasing behavior among Jumia consumers in Ilaro, Ogun State, Nigeria (R = 0.703, R² = 0.495, p 0.001). Specifically, social proof (β = 0.444, p 0.001) and emotional triggers (β = 0.372, p 0.001) were significant predictors of consumer purchasing behavior among Jumia consumers in Ilaro, Ogun State, Nigeria. The research contributes to the digital marketing and consumer behavior literature by empirically validating digital psychology constructs within a Nigerian context. It offers a recommendation for digital retailers that states social proof and emotionally engaging content should be strategically integrated into consumer interactions.